Subnational impacts of NAFTA's environmental regime: a comparative analysis of Canada, the United States, and Mexico - Duncan, Pamela, author; Mumme, Stephen, advisor (Colorado State University. Libraries, 2003)
This dissertation presents a comparative analysis of the impacts of the North American Free Trade Agreement's (NAFTA) environmental regime on the states and provinces of the U.S., Canada and Mexico. It compares the federalism arrangements of the three NAFTA parties and analyzes the environmentally relevant aspects of the NAFTA text as well as its environmental side agreement, the North American Agreement on Environmental Cooperation (NAAEC). The dissertation presents case studies of constraints presented to the states and provinces under the investment rules of NAFTA's Chapter Eleven and the citizen submissions process of Articles 14 and 15 of the NAAEC. It also examines potential opportunities presented to the states by the regime, especially the Commission for Environmental Cooperation (CEC). The dissertation concludes that, despite significant variations in federalism arrangements among the NAFTA parties, the states and provinces face similar constraints under the environmental regime. In addition, the subnational governments have generally not availed themselves of the opportunities presented by the regime. Based on these findings, the dissertation speculates that federalism may be losing relevance in the context of new international trade rules.
Keywords: political science; social impact; comparative analysis